On the Utilization of Circle Grid Analysis in Thin-walled Forming of Tubes: Experimental and Numerical Evaluation. (2017) - Centeno, G; Silva, M.B.; Alves, L.M.; Vallellano, C.; Martins, P.A.F.
Abstract: This paper presents an investigation on different tube forming processes by plastic deformation, including expansion, reduction and inversion of tube ends, using circle grid analysis in order to obtain strain-loading paths in different regions of the principal strain space. The experimental work was carried out on commercial AA6063-T6 tubes and includes independent material characterization by means of tensile, stack compression and instability tests. Finite element modelling of the tube forming processes by means of an in-house computer program gives support to the presentation and allows assessing the overall accuracy, validity and reliability of using circle grid analysis to investigate formability and failure in tube forming.